Case Report First-in-Man Method Description: Left Ventricular Unloading With iVAC2L During Veno-Arterial Extracorporeal Membrane Oxygenation: From Veno-Arterial Extracorporeal Membrane Oxygenation to ECMELLA to EC-iVAC® - Tschöpe, Carsten; Alogna, Alessio; Faragli, Alessandro; Klingel, Karin; Schmidt, Gunther; Heilmann, Torsten Wolfgang; B. Bastos, Marcelo; Spillmann, Frank (Frontiers in Cardiovascular Medicine, 2020)
Veno-arterial extracorporeal membrane oxygenation (V-A ECMO) is increasingly used in cardiogenic shock patients with bi-ventricular failure to maintain systemic perfusion. However, the increase in afterload and the overload of left ventricle (LV) are major drawbacks of V-A ECMO. To avoid these negative effects, an additional LV venting strategy with an Impella CP (3.5 L/min cardiac output support) was used in a patient with cardiogenic shock and severe acute myocarditis (ECMELLA- approach). After a hemolysis crisis, the Impella® device has been substituted with an iVAC 2L® catheter to obtain LV unloading with pulsatile flow. An improvement in LVEF and LVEDD together with a reduction of free hemoglobin have been observed, showing a potential application of iVAC 2L in patients with cardiogenic shock and increased hemolysis.